New models of large-cell neuroendocrine carcinoma and small-cell lung carcinoma - Santos, Mirentxu (Mol Cell Oncol, 2020)
High-grade neuroendocrine lung carcinomas (LCNEC, SCLC) are recalcitrant cancers for which no optimal management has been achieved. We have recently described two models of LCNEC and SCLC developed upon inactivation of 4 tumor suppressors genes (Rb1 (RB transcriptional corepressor 1), Rbl1 (RB transcriptional corepressor like 1), Pten (phosphatase and tensin homolog), Trp53 (transformation-related protein 53), which provide a suitable frame for preclinical intervention. A defined model for LCNEC had not been previously reported.